Facing the giants - Kendrick, Alex, 1970-; Kendrick, Stephen; Blackwell, James; Cave, Bailey; Fields, Shannen; Goode, Tracy; Destination Films; Samuel Goldwyn Films; Sherwood Pictures; Provident Films; Carmel Entertainment; Kendrick Brothers; et al. ([Australia] : Sony Pictures Home Entertainment (distributor), 2007)
From the award winning producers of FLYWHEEL, comes an action-packed drama about a Christian high school football coach who uses his undying faith to battle the giants of fear and failure. In six years of coaching, Grant Taylor has never led his Shiloh Eagles to a winning season. After learning that he and his wife Brooke face infertility, Grant discovers that a group of fathers are secretly organizing to have him dismissed as head coach. Devastated by his circumstances, he cries out to God in desperation. When Grant receives a message from an unexpected visitor, he searches for a stronger purpose for his football team. He dares to challenge his players to believe God for the impossible on and off the field. When faced with unbelievable odds, the Eagles must step up to their greatest test of strength and courage. What transpires is a dynamic story of the fight between faith and fear. Facing the Giants is a powerful experience for the whole family inspiring viewers to live with faith, hope, and love!
Screenplay by Alex Kendrick, Stephen Kendrick ; directed by Alex Kendrick.
James Blackwell, Bailey Cave, Shannen Fields, Tracy Goode, Alex Kendrick.
Censorship classification: PG.
PAL ; Region 4.
In English, French, Italian, Spanish with subtitles in English, English captions, French, Italian, Spanish, Arabic, Dutch, Hindi, Portuguese.
Keywords: Football coaches -- United States -- Drama; School sports -- United States -- Drama; Fertility, Human -- Drama; Feature films; Video recordings for hard of hearing people